2017
DOI: 10.21608/jfds.2017.38892
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Fat – Soluble Vitamins and Natural Antioxidants in Seventeen Vegetable Oils

Abstract: The fat-soluble vitamins (A, D, E and K) and the most natural antioxidants (T.polyphenols, tocopherols, chlorophylls, carotenoids, δ-oryzanol, phenolic and flavonoid compounds) of seventeen vegetable oils (olive, corn crystal, corn lecuir, sunflower, palm olein, soybean, linseed, cottonseed, sesame, rice bran, peanut, blending, wheat germ, safflower, rapeseed, castor and coconut oils) were estimated. Results showed that, parameters established (acidity, peroxide value, K232 and 270nm.) to measure level of qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 5 publications
3
5
0
Order By: Relevance
“…Carotenoids content found in castor oil ranged from 12.34-39.47 mg/kg β-carotene oil (Kadri et al, 2011). In another study, the carotenoids identified in castor oil was 2.05 mg/kg oil (Atta & Mohamed, 2017). Comparing with other vegetable oils, the carotenoid content of castor oil is higher than soybean with 0.37 mg/kg oil and safflower at 1.21 mg/kg oil (Atta & Mohamed, 2017).…”
Section: Carotenoidsmentioning
confidence: 92%
See 2 more Smart Citations
“…Carotenoids content found in castor oil ranged from 12.34-39.47 mg/kg β-carotene oil (Kadri et al, 2011). In another study, the carotenoids identified in castor oil was 2.05 mg/kg oil (Atta & Mohamed, 2017). Comparing with other vegetable oils, the carotenoid content of castor oil is higher than soybean with 0.37 mg/kg oil and safflower at 1.21 mg/kg oil (Atta & Mohamed, 2017).…”
Section: Carotenoidsmentioning
confidence: 92%
“…In another study, the carotenoids identified in castor oil was 2.05 mg/kg oil (Atta & Mohamed, 2017). Comparing with other vegetable oils, the carotenoid content of castor oil is higher than soybean with 0.37 mg/kg oil and safflower at 1.21 mg/kg oil (Atta & Mohamed, 2017). Mostly, at higher temperature carotenoid content easily degrade, and this might contribute to the low carotenoid in the oils.…”
Section: Carotenoidsmentioning
confidence: 95%
See 1 more Smart Citation
“…Then, powders of the natural additives were incorporated into neat castor oil ( CO ) which was acquired from Abreiko, Guadalajara (Jalisco), Mexico. It was reported that castor oil contains a natural concentration of some carotenoids of about 2.05 mg/kg [ 16 ]. In this study, a molal concentration of 0.001 (approximately 568 mg/kg) of each xanthophyll was fixed, based on a previous laboratory solubility test.…”
Section: Methodsmentioning
confidence: 99%
“…Vegetable oils contain some natural antioxidants like polyphenols, tocopherols, carotenoids, chlorophyll, and δ–oryzanol [ 16 ], but the amounts thereof are not enough to allow the good oxidative capacity required for their use as industrial lubricants. Carotenoids are natural fat-soluble compounds that are made up of multiple isoprene units with a substituted and unsaturated cyclohexane ring at each termination [ 17 ].…”
Section: Introductionmentioning
confidence: 99%